Maintenance of photosynthetic capacity in flooded tomato plants with reduced ethylene sensitivity - de Pedro, Leandro Federico (2020)
Ethylene is considered one of the most important plant hormones orchestrating plant responses to flooding stress. However, ethylene may induce deleterious effects on plants, especially when produced at high rates in response to stress. In this paper, we explored the effect of attenuated ethylene sensitivity in the Never ripe (Nr) mutant on leaf photosynthetic capacity of flooded tomato plants. We found out that reduced ethylene perception in Nr plants was associated with a more efficient photochemical and non-photochemical radiative energy dissipation capability in response to flooding. The data correlated with the retention of chlorophyll and carotenoids content in flooded Nr leaves. Moreover, leaf area and specific leaf area were higher in Nr, indicating that ethylene would exert a negative role in leaf growth and expansion under flooded conditions. Although stomatal conductance was hampered in flooded Nr plants, carboxylation activity was not affected by flooding in the mutant, suggesting that ethylene is responsible for inducing non-stomatal limitations to photosynthetic CO2 uptake. Upregulation of several cysteine protease genes and high protease activity led to Rubisco protein loss in response to ethylene under flooding. Reduction of Rubisco content would, at least in part, account for the reduction of its carboxylation efficiency in response to ethylene in flooded plants. Therefore, besides its role as a trigger of many adaptive responses, perception of ethylene entails limitations in light and dark photosynthetic reactions by speeding up the senescence process that leads to a progressive disassembly of the photosynthetic machinery in leaves of flooded tomato plants.